The Culture of Drinking Herbal Medicine in Pregnant Women: A Phenomenological Study - Fadlilah, Nazilatul; Shrimarti Rukmini Devy; Mohammad Zainal Fatah; Mangestuti Agil; Ahmaniyah (Universitas Airlangga, 2023)
Background: Pregnant women who drink herbal medicine can increase the risk of meconium amniotic fluid, and meconium amniotic fluid is a risk factor for asphyxia in newborns. Objectives: Identify three forms of culture in drinking herbal medicine in pregnant women, namely the mother's values and ideas about drinking herbal medicine, herbal drinking activities, and material on the culture of drinking herbal medicine. Methods: This research is a qualitative method with a phenomenological approach. Informants in this study consisted of pregnant women and key informants consisted of families of pregnant women, cadres, ustadzah, midwives, and herbal medicine providers. Results: The cultural forms of drinking herbal medicine include: 1) Values and Ideas. Drinking herbal medicine for pregnant women is still practiced because of their subjective norms and normative beliefs from the surrounding environment. All informants believed that herbal medicine could provide benefits rather than negative effects, and only midwives stated that herbal medicine had negative effects, namely meconium amniotic fluid, and even asphyxia. 2) The activity of drinking herbal medicine. Pregnant women drink herbal medicine from the beginning of pregnancy until delivery. The frequency of taking herbal medicine was various. Religious figures and community leaders have an important role in the culture of drinking herbal medicine. 3) Herbal ingredients. The herbs consumed by each informant were different, there were informants who consumed homemade herbs and bought them at the market. Conclusions: The culture of drinking herbal medicine is still carried out because the local community's belief about the benefits of herbal medicine is still high, and lack of public knowledge about the effects of drinking herbal medicine on pregnant women.